PENINGKATAN KETERAMPILAN SOSIAL SISWA DENGAN MENGGUNAKAN MODEL COOPERATIVE LEARNING TIPE MAKE A MATCH PADA MATA PELAJARAN IPAS DI SEKOLAH DASAR: (Penelitian Tindakan Kelas Pada Siswa Kelas V UPT SD Negeri 016 Bangkinang Kota Bab 6 Indonesiaku Kaya Raya) - Septhiana, Delly; Rizal, Muhammad Syahrul; Mufarizuddin; Ananda, Rizki; Pebriana, Putri Hana (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research was motivated by the low social skills of class V students at UPT SD Negeri 016 Bangkinang Kota. This research aims to improve the social skills of class V UPT SD Negeri 016 Bangkinang Kota students totaling 27 students. The research used was Classroom Action Research (PTK) which was carried out in two learning cycles. Each cycle consists of two meetings and four learning stages, namely: planning, implementation, observation and reflection. The research was carried out in May 2024. Data collection techniques were in the form of observation and documentation. Meanwhile, data analysis techniques use qualitative analysis and quantitative analysis. Based on the results of data analysis, the social skills results of class V UPT SD Negeri 016 Bangkinang Kota students in pre-action were obtained with a learning completion percentage of 30%. In cycle I, meeting I, the percentage of learning completeness was 48% and in cycle I, meeting II experienced an increase with a percentage of learning completeness of 59%. In cycle I, meeting I also experienced an increase with a learning completion percentage of 67% and in cycle II meeting II experienced another increase with a learning percentage of 89%. Thus it can be concluded that by implementing the Make A Match Type Cooperative Learning model, it can improve the social skills of class V students at UPT SD Negeri 016 Bangkinang Kota.